Lights and shadows on the resonant modes of the Earth rotation axis - Bizouard, C. (2025)
Resonant free modes are of primary important for understanding the terrestrial and celestial oscillations of the rotation axis of a non-rigid Earth. In this talk we present the state of the art of their observation and modeling. We show how mass transports taking place in the hydro-atmospheric layer allows to reconstruct Chandler wobble from the 1950’s, and account in particular for its minimum observed since the 2020. In contrast, the irregularities of the free core nutation remains largely unexplained. Until now, diurnal circulation in the atmosphere and oceans seems to have been powerless, and we shall give the last results in this respect. Finally we shall explore the existence of a supplementary polar motion resonance caused by the inner core.